Pengaruh Strategi Pembelajaran Crossword Puzzle terhadap Hasil Belajar pada Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Siswa Kelas V di SD Negeri 46 Kota Pagar Alam - Ramadhani, Yolanda; Kariyanto, Hendi (MODELING: Jurnal Program Studi PGMI, 2024)
This research aims to determine the effect of the crossword puzzle learning strategy on learning outcomes in social studies subjects for class V students at SD Negeri 46 Kota Pagar Alam. This type of research is quantitative with an experimental method, a pre-experiment design, a one-group pretest-posttest design. The sampling technique uses purposive sampling. The number of samples was 24 students. Data collection techniques are observation, interviews, tests and documentation. The results of this research showed that the average score for the pre-test was 40.00 and the post-test was 75.83. The data analysis technique used for the normality test was Shapiro-Wilk and the homogeneity test used Levene's. Based on the results of hypothesis testing using paired samples t-test, it was obtained that tcount was 24.474 ≥ ttable 2.069, meaning THAT there was a significant influence of the crossword puzzle learning strategy on learning outcomes in social studies subjects for class V students at SD Negeri 46 Kota Pagar Alam. The magnitude of the influence of the crossword puzzle learning strategy on social studies learning outcomes has been calculated using a coefficient of determination of 78%, meaning that social studies learning outcomes are influenced by the crossword puzzle learning strategy.